Fourier-Domain Phase Retardation Vortex Measurement - Schovánek Petr; Baránek Michal; Bouchal Petr; Bouchal Zdeněk (EPJ Web of Conferences, 2023)
Optical vortices have found a wide range of applications thanks to their helical phase topology allowing to carry the orbital angular momentum. In this work, self-interfering vortex beams are utilized in a new single-shot holographic method for the circular phase retardation measurement. The vortices carrying information about the phase retardation introduced between two orthogonal circular polarization modes are generated by the spin to orbital angular momentum conversion. The phase retardation is stored in off-axis holographic records acquired in a common-path setup using a geometric-phase grating. In the proposed method, the circular phase retardation is reconstructed in the Fourier domain, surpassing the measurement precision provided by methods restoring the retardation from the rotation of a Double-Helix Point Spread Function (DH PSF). The developed method can be adapted for application to polarimetry, orientation imaging and diagnostics of nano-emitters.